Cubic and orthorhombic Cd2SnO4 microcrystals: molten salt synthesis, phase evolution and dye degradation studies. (11th September 2019) - Preethi, G; Balan, Ramdas; Koppala, Sivasankar; Nagaswarupa, H P
Abstract: Herein, we report the facile preparation of Cd2 SnO4 microcrystals in two different crystal structures i.e. cubic and orthorhombic by using a eutectic mixture of NaCl-KCl in the molten salt synthesis method. The starting materials with eutectic salts were calcined at 900 °C for different durations to study the phase evolution. XRD pattern and Raman spectra confirmed the single-phase cubic structure for a soaking period of 15 min and orthorhombic structure for 6 h. Flame photometry studies showed no traceable amount of Na and K incorporated in the lattice of the prepared Cd2 SnO4 . SEM micrograph reveals that cubic and orthorhombic Cd2 SnO4 compounds in polygonal and rod shape morphology respectively. The dye degradation efficiency of the cubic and orthorhombic Cd2 SnO4 were studied under UV irradiation for Rhodamine B as a model dye. The results confirm that cubic structure shows higher degradation ability compare to orthorhombic Cd2 SnO4 due to lower recombination of the electron-hole pairs, which is supported by PL spectra.